2011
DOI: 10.1111/j.1742-481x.2011.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the open abdomen with topical negative pressure therapy: a retrospective study of 46 cases

Abstract: The open abdomen is an ongoing challenge for professionals engaged in its treatment. The change in the integrity of the abdominal wall, the loss of fluids, heat and proteins and contamination of the wound are the main problems. The objective of this article is to describe our experience using the abdominal dressing vacuum-assisted closure therapy in treatment of the open abdomen. Since December 2006, all patients requiring treatment with the open abdomen technique have been treated with the abdominal dressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
(22 reference statements)
1
23
0
5
Order By: Relevance
“…Analysing the type of cycle of negative pressure therapy, we surprisingly found that the spontaneous closure rate was 70% (7 of 10 EAFs) using intermittent settings of negative pressure, whereas in the group of patients treated with continuous pressure, 57% of EAFs closed spontaneously (12 of 21 EAFs). The mean number of NPWT dressing was 9 (SD 3⋅3; range [4][5][6][7][8][9][10][11][12][13][14][15][16]. Three patients died (18⋅8%) during NPWT in OA management.…”
Section: Resultsmentioning
confidence: 99%
“…Analysing the type of cycle of negative pressure therapy, we surprisingly found that the spontaneous closure rate was 70% (7 of 10 EAFs) using intermittent settings of negative pressure, whereas in the group of patients treated with continuous pressure, 57% of EAFs closed spontaneously (12 of 21 EAFs). The mean number of NPWT dressing was 9 (SD 3⋅3; range [4][5][6][7][8][9][10][11][12][13][14][15][16]. Three patients died (18⋅8%) during NPWT in OA management.…”
Section: Resultsmentioning
confidence: 99%
“…Post‐operative measures range from conventional dressing of sterile dry gauzes , debriding agents and topical antimicrobial dressing, to more advanced wound dressings in an effort to stimulate the proliferative phase of wound healing, including hydrocolloids , topical application of autologous blood products , growth factors , cultured skin and Negative Pressure Wound Therapy (NPWT) . The evidence that supports the benefits of Negative Pressure Wound Vacuum Therapy in improving healing, as an adjunctive therapy, in the management of difficult open wounds, has been widely described in literature ; however, its application in closed incisions is not characterised so well. Since the introduction of this portable and practical device in clinical practise in the 1990s, the acute and chronic open wounds management's landscape has been dramatically revolutionised .…”
Section: Introductionmentioning
confidence: 99%
“…Post-operative measures range from conventional Key Messages • underlying patient comorbidities in addition to surgical-related factors often make the management of surgical wounds primary closure challenging because of the higher risk of developing complications • surgical incision complications include post-operative surgical site infections, surgical wound dehiscence, formation of hematomas and seromas, skin and fat necrosis and skin and fascial dehiscence or blistering • Iincisional Negative Pressure Wound Therapy seems to be a useful prophylactic measure in the incidence of infection and sero-hematoma formation and in decreasing re-operation rates when applied over closed surgical incisions and so can be considered to be potentially cost saving especially in high-risk patients dressing of sterile dry gauzes (5), debriding agents and topical antimicrobial dressing, to more advanced wound dressings in an effort to stimulate the proliferative phase of wound healing, including hydrocolloids (5), topical application of autologous blood products (30), growth factors (31), cultured skin (32) and Negative Pressure Wound Therapy (NPWT) (3,6,33). The evidence that supports the benefits of Negative Pressure Wound Vacuum Therapy in improving healing, as an adjunctive therapy, in the management of difficult open wounds, has been widely described in literature (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46); however, its application in closed incisions is not characterised so well.…”
Section: Introductionmentioning
confidence: 99%
“…The use of vacuum‐assisted suction dressings in the management of these wounds may impart several distinct advantages in addition to wound coverage, protection of the exposed viscera, and assisting with fascial closure. First, these dressings contribute to a decrease in fluid losses across the open wound surfaces by significantly reducing evaporation 12 . Second, a closed‐suction dressing draining into a dedicated canister facilitates fluid collection and allows a more accurate estimation of fluid losses from the wound and peritoneal cavity 7 .…”
Section: Fluid and Electrolyte Managementmentioning
confidence: 99%